Association Between 'Wind‐Test' Findings and Resting Endoscopic Assessment of Laryngeal Function at Thoroughbred Public Auction in the UK. (September 2014) - Palmer, L.; Ramzan, P.
Abstract : Reasons for performing study: Despite ongoing advances in diagnostic imaging, 'wind‐testing' remains the most common screening test for upper respiratory tract obstructions and is an important condition of sale at Thoroughbred public auctions in UK/Europe. Correlations between abnormal respiratory noise and resting laryngeal function have been incompletely investigated to date. Objectives: To determine whether associations exist between respiratory noise at lunge and subsequent diagnosis of recurrent laryngeal neuropathy (RLN). Study design: Retrospective analysis of records for all post sale wind‐testing undertaken by a single veterinary practice at Tattersalls Newmarket yearling, breeze‐up and horse‐in‐training sales between 2009 and 2013. Methods: Descriptions of abnormal respiratory noise were categorised as 'inspiratory whistle', 'inspiratory harsh' or 'pan‐respiratory harsh', and included lunge direction during which noise was evident. Concurrent examination by 2 veterinary surgeons was a criterion for inclusion of cases. All horses making abnormal respiratory noises underwent resting endoscopy with a consensus score (Lane scale) given for laryngeal function. Results: 2972 horses underwent post sale wind‐testing and 418 horses (14.1%) underwent resting endoscopic examination due to abnormal respiratory noise. Likelihood of making an abnormal respiratory noise differed significantly between groups (yearlings 10.8%, 'breeze‐up' 2‐year‐olds 20.6%, horses‐in‐training 30.1%). Yearlings were significantly more likely (P<0.0001, Chi‐squared/Bonferroni test) to make a 'harsh' respiratory noise than horses‐in‐training. Type of noise (whistle) was significantly associated with resting endoscopic evidence of RLN in yearlings (P = 0.009); specificity of 'whistle' for RLN in this group was 38.6%. There was no association between lunge direction noise (left, right or both) and RLN. Conclusions: These results support the widespread belief that harsh respiratory noise when lunged of presumed 'palatal/pharyngeal' origin is more likely in yearlings than horses‐in‐training, possibly due to upper respiratory inflammation or immaturity. Inspiratory whistle in both lunge directions is no stronger an indicator of RLN than unidirectional whistle. Ethical animal research: Ethical committee oversight not currently required by this congress: retrospective study of clinical records. Explicit owner informed consent for participation in this study was not stated.Sources of funding: None.Competing interests: None.